(untitled) (Palíndromo, 2025)
This article addresses the nuances of the institutionalization of contemporary art, in order to report the perpetuation of an unified and white-patriarchal art history, as well as to demonstrate the decentralization of legitimizing means in the instant information and repro-duction era, based on the case study on the episode of veto by Correios Cultural Center on the artwork And sometimes it almost seems that I’m not using that crown of thorns (own translation), a reinterpretation of The Last Supper by Leonardo da Vinci, by Elvira Freitas Lira, who subverts the mythical image of the scene. It also seeks to inquire, through bibliographic and iconographic research and deep observation on a particular reading, the pictorial and conceptual elements and your distinctions of the beautiful, based on the comparison be-tween the renaissance and contempo-rary painting, which could have unset-tled the moral structures of the said art institution. It’s possible to attest, based on the presented studies, that holders of power, social and economic, aim to remain at the top of the hierarchy pyr-amid, deploying censorship for those who report them and even taking pos-session of plural speeches to their own benefit. Furthermore, it deduces that the Internet becomes a contemporary and democratic legitimizing mean, cast-ing doubt on the hierarchic structures.